1992
DOI: 10.1093/clinids/14.5.1149
|View full text |Cite
|
Sign up to set email alerts
|

A Clinico-Epidemiological Study of Epidemic Typhus in Africa

Abstract: Epidemic, louse-borne typhus persists in the rugged, mountainous areas of Ethiopia and much of northeastern and central Africa as well as in the rural highlands of Central and South America, where the conditions of living favor the harboring of body lice and where antibiotic treatment and effective louse-control measures are unavailable. The historical significance and current epidemiology of typhus, including the reservoir of Rickettsia prowazekii in flying squirrels in the United States, are reviewed, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…It is still prevalent in areas where poor socioeconomic conditions and a high prevalence of louse infestations exist. The recent circulation or distribution of epidemic typhus is indefinite but since the 1990s, foci of epidemic typhushave been described in Africa, including Algeria (Mokrani et al, 2004) and central eastern African countries such as Ethiopia, Zaire, Rwanda and Burundi (Perine et al, 1992), in mountainous regions of South America (including Peru), in mountainous or highland regions of North America, in the Himalayan regions in Asia, and in Russia (Tarasevich et al, 1998). An autochthonous case of epidemic typhus has been recently reported in France (Badiaga and Brouqui, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is still prevalent in areas where poor socioeconomic conditions and a high prevalence of louse infestations exist. The recent circulation or distribution of epidemic typhus is indefinite but since the 1990s, foci of epidemic typhushave been described in Africa, including Algeria (Mokrani et al, 2004) and central eastern African countries such as Ethiopia, Zaire, Rwanda and Burundi (Perine et al, 1992), in mountainous regions of South America (including Peru), in mountainous or highland regions of North America, in the Himalayan regions in Asia, and in Russia (Tarasevich et al, 1998). An autochthonous case of epidemic typhus has been recently reported in France (Badiaga and Brouqui, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating clinical signs of epidemic typhus from other febrile illnesses is difficult. Although previous clinical studies have identified a rash in over 50% of cases, 6 only about a quarter of the patients presented with a rash during this outbreak, highlighting the limited value of the rash in enhancing clinical suspicion. All seven reported deaths occurred earlier in the outbreak.…”
Section: Discussionmentioning
confidence: 63%
“…4,5 Epidemic typhus occurs most commonly among people living in overcrowded settings with suboptimal hygiene conditions. 6,7 The most affected populations are those living in impoverished conditions, areas of war or natural disasters, refugee camps, and areas with colder mountainous regions. 4,8 Epidemic typhus is rare but severe when it occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In addition, outbreaks of louse-borne typhus took place in the highlands of Ethiopia in the past, and a recent report showed a prevalence of 5% of positive Weil Felix tests among febrile children in northwest Ethiopia. 15,25 Nonetheless, our study is among the few studies using highly sensitive and specific real-time PCR methods to describe the presence of Rickettsia spp. in Ethiopia.…”
Section: Discussionmentioning
confidence: 95%